Neuropsychiatric symptoms in untreated Parkinson’s disease - Szatmari S (Dove Medical Press, 2017)
Szabolcs Szatmari,1–3 Ben Min-Woo Illigens,4 Timo Siepmann,5,6 Alexandra Pinter,5,7 Annamaria Takats,8 Daniel Bereczki8 1Department of Neurology, Sibiu County Emergency Hospital, Sibiu, 22nd Department of Neurology, Targu Mures Emergency Clinical County Hospital, Targu Mures, Romania; 3János Szentágothai Doctoral School of Neurosciences, Semmelweis University, Budapest, Hungary; 4Department of Neurology, Beth Israel Deaconess Medical Center, Harvard Medical School, Boston, MA, USA; 5Center for Clinical Research and Management Education, Division of Health Care Sciences, Dresden International University, 6Department of Neurology, University Hospital Carl Gustav Carus, Technical University of Dresden, Dresden, Germany; 7Department of Family Medicine, 8Department of Neurology, Semmelweis University, Budapest, Hungary Abstract: Neuropsychiatric and cognitive symptoms are common in Parkinson’s disease (PD) and may precede and exceed motor symptoms as major factors impacting disease course and quality of life. Neuropsychiatric symptoms (NPS) in PD are various and are attributed to pathologic changes within multiple brain regions, to psychological stress, and to adverse effects of dopamine replacement therapy. Sleep disorders and mood symptoms such as apathy, depression, and anxiety may antedate the development of motor symptoms by years, while other NPS such as impulse control disorders, psychosis, and cognitive impairment are more common in later stages of the disease. Few studies report on NPS in the early, untreated phase of PD. We reviewed the current literature on NPS in PD with a focus on the early, drug-naive stages of PD. Among these early disease stages, premotor and early motor phases were separately addressed in our review, highlighting the underlying pathophysiological mechanisms as well as epidemiological characteristics, clinical features, risk factors, and available techniques of clinical assessment. Keywords: neuropsychiatric symptoms, Parkinson’s disease, untreated